Antropometrie als instrument voor de geneeskunst. Onderzoek en publicaties van Nederlandse medici (1849–1869) - Tassenaar, Vincent (Studium, 2014)
This research focuses on the Dutch publications about human height in the middle of the nineteenth century. Some of these articles, especially those of Johannes Zeeman, drew the attention of physicians and anthropometric historians in the twentieth century. This article presents an overview of these publications and the effects of these publications afterwards. In 1848 there was a shift in government policy which was accompanied by an upstart of several professional societies. It became the heyday of the hygienists, a group of physicians who believed in public health. Some of these hygienists presented themselves in their new medical professional society the Nederlandsche Maatschappij tot bevordering der Geneeskunst (Dutch Society of Medicine) especially in the committee for statistics. Until now there has been only limited attention for their scientific publications. Since mortality figures were unavailable, the members of the statistical committee started to analyse military data with stature as proxy for health. In a short period of one and a half decade a high standard of these articles was reached. In this article the rise and downfall of this first Golden age of anthropometrics will be placed in scientific and social developments.